2005
DOI: 10.1212/01.wnl.0000150935.05940.2d
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of predictors of poststroke depression

Abstract: In the stroke unit, crying and overt sadness are more reliable indicators of depressed mood than apathy. In patients with first-ever stroke, crying behaviors soon after stroke, a younger age, and severe disability are predictors of poststroke depression occurrence within the first year after stroke onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
98
3
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 46 publications
(29 reference statements)
10
98
3
8
Order By: Relevance
“…Catastrophic reactions and pseudobulbar affect are hard to distinguish from one another, as they have similar symptoms 2,10 ; patients present with outbursts of emotion (e.g., sudden crying, anger or aggression, uncontrollable laughing, or sudden surges of anxiety). The differences are related more to their triggers than to the behaviors associated with them.…”
Section: What Are the Psychological Reactions To Stroke And When Do Tmentioning
confidence: 99%
See 4 more Smart Citations
“…Catastrophic reactions and pseudobulbar affect are hard to distinguish from one another, as they have similar symptoms 2,10 ; patients present with outbursts of emotion (e.g., sudden crying, anger or aggression, uncontrollable laughing, or sudden surges of anxiety). The differences are related more to their triggers than to the behaviors associated with them.…”
Section: What Are the Psychological Reactions To Stroke And When Do Tmentioning
confidence: 99%
“…10 Catastrophic reactions, a term first coined by Goldstein,17 are defined as the intense emotional reactions that patients have when presented with a task that they are unable to perform due to neurologic deficits. 10 Research has found that catastrophic reactions are prevalent and related to lesion location; they occur in about 4% to 20% of stroke survivors. 11,18 Denial of physical impairment can also lead to catastrophic reactions: when denial fails, anger arises.…”
Section: What Are the Psychological Reactions To Stroke And When Do Tmentioning
confidence: 99%
See 3 more Smart Citations